2018
DOI: 10.3390/ijms19092786
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the OAS Gene Family Is Highly Modulated in Subjects Affected by Juvenile Dermatomyositis, Resembling an Immune Response to a dsRNA Virus Infection

Abstract: Background: Juvenile dermatomyositis (JDM) is a systemic, autoimmune, interferon (IFN)-mediated inflammatory muscle disorder that affects children younger than 18 years of age. JDM primarily affects the skin and the skeletal muscles. Interestingly, the role of viral infections has been hypothesized. Mammalian 2′-5′-oligoadenylate synthetase (OAS) genes have been thoroughly characterized as components of the IFN-induced antiviral system, and they are connected to several innate immune-activated diseases. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 75 publications
3
13
0
Order By: Relevance
“…In the present study, we found that interferon-stimulated genes were significantly upregulated in JDM patients, as well as the so-called "interferon signature", demonstrating a possible mechanism that viral mimics or other stimuli may play a crucial role in the pathogenesis of JDM. Viral mimics are thought to participate in the pathogenesis of JDM (Musumeci & Castrogiovanni 2018) and other autoimmune diseases (Christen et al 2004;Sellami et al 2019), consistent with the notion that JDM patients have higher rates of viral infections (Tansley et al 2013;Zheng et al 2019). This may suggest that the prevention of certain viral infections would decrease the incidence of autoimmunity by inhibiting self-antigenic mimics.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, we found that interferon-stimulated genes were significantly upregulated in JDM patients, as well as the so-called "interferon signature", demonstrating a possible mechanism that viral mimics or other stimuli may play a crucial role in the pathogenesis of JDM. Viral mimics are thought to participate in the pathogenesis of JDM (Musumeci & Castrogiovanni 2018) and other autoimmune diseases (Christen et al 2004;Sellami et al 2019), consistent with the notion that JDM patients have higher rates of viral infections (Tansley et al 2013;Zheng et al 2019). This may suggest that the prevention of certain viral infections would decrease the incidence of autoimmunity by inhibiting self-antigenic mimics.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, we found that interferon-stimulated genes were significantly upregulated in JDM patients, as well as the so-called ''interferon signature'', demonstrating a possible mechanism that viral mimics or other stimuli may play a crucial role in the pathogenesis of JDM. Viral mimics are thought to participate in the pathogenesis of JDM (Musumeci & Castrogiovanni, 2018) and other autoimmune diseases (Christen et al, 2004;Sellami et al, 2019), consistent with the notion that JDM patients have higher rates of viral infections (Tansley, McHugh & Wedderburn, 2013;Zheng et al, 2019). This may suggest that the prevention of certain viral infections would decrease the incidence of autoimmunity by inhibiting self-antigenic mimics.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, the IFNG signaling pathways were significantly involved through the expression of 23 genes out of 189 available (p = 5.19 × 10 −22 , 12.1%) ( Figure 1d) ( Supplementary Table S1). In our analysis, we also observed several antiviral response activated pathways, such as the double-strand RNA virus (OAS1, OAS2 and OAS3) (three out of nine genes; p = 0.00066, 33.3%) [40][41][42][43][44], the Herpes simplex (14 out of 181 genes; p = 1.10 × 10 −10 , 7.7%), and Influenza A virus (10 out 168 genes; p = 5.29 × 10 −7 , 5.9%) ( Supplementary Table S1). These specific activated pathways could be due to the IFNG signaling.…”
Section: Identification Of Potential Genes Modulated In Jak 2v617f Musupporting
confidence: 52%